APPLICATION OF EXTRATERRITORIAL JURISDICTION IN EUROPEAN CONVENTION ON HUMAN RIGHTS (CASE STUDY: AL-SKEINI AND OTHERS V. UK) - Sitepu, Aldo Ingo (Indonesian Journal of International Law, 2016)
This research explains the definition of jurisdiction, development of the extraterritorial jurisdiction and its regulation in international law which includes its principle and also boundaries. This research then analyses cases before Al- Skeini and others v. UK case regarding the application of jurisdiction mentioned in Article 1 of the European Convention on Human Rights (ECHR) by European Court of Human Rights (ECtHR). Furthermore, this research analyses the applications of Article 1 ECHR in United Kingdom’s House of Lords decision and ECtHR decision in Al-Skeini. In its decision ECtHR stated that the existence of Public Power in Al-Skeini causes an extraterritorial jurisdiction in that case. The judgement caters to the human rights protection but on the other hand it still leaves confusion in determining the requirement of extraterritorial jurisdiction in the ECHR.